High Prevalence of Hepatitis C Virus Infection in Primitive Tribes of Eastern India and Associated Sociobehavioral Risks for Transmission: A Retrospective Analysis - Shantanu Kumar Kar (Mary Ann Liebert, 2019)
Purpose: The primitive tribal groups (PTGs) need special attention because of their low population growth: declining population size with high mortality rates. Scanty reports are available on the prevalence of hepatitis C virus (HCV) infection in primitive tribes of the country emphasizing their cultural and social practices associated with transmission of the disease. Methods: The study was conducted on 1765 tribal individuals covering 5 PTGs, namely Lodha, Saora, Khadia, Juanga, and Mankidia, from 6 districts of Odisha. Serum samples were tested for the anti-HCV antibody using commercially available enzyme immunoassays. HCV RNA was detected based on the 5? NCR region and genotyping was done by direct sequencing of the core region. Potential risk factors for HCV transmission were collected using a questionnaire and subjected to regression analysis through SPSS, version 17.0. Results: Antibody to HCV was detected in 0%, 3.3%, 5.7%, 8.5%, and 13.4% in Saora, Lodha, Khadia, Juanga, and Mankidia tribes, respectively. HCV RNA was detected in 8.6% (11/127) of the samples tested. Genotyping of HCV isolates in all HCV RNA-positive samples revealed genotype 1b. Sharing of razors and shaving by the village barber were found to be significantly (p<0.05) associated with HCV transmission in males, whereas tattooing and multiple injections were found to be significant risk factors for females. Conclusion: This study indicated a high prevalence of HCV infection in Mankidia and Juanga tribes in comparison with the national scenario, which needs public health attention.